Governing the extractive sector : regulating the foreign conduct of international mining firms - Bone, Jeffrey (Writer on international mining firms) (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This book considers, and offers solutions to, the problems faced by local communities and the environment with respect to global mining. The author explores the idea of grievance mechanisms in the home states of the major mining conglomerates. These grievance mechanisms should be functional, pragmatic and effective at resolving disputes between mining enterprises and impacted communities. The key to this provocative solution is two-fold: the proposal harnesses the power of industry-sponsored dispute mechanisms to reduce the costs and other burdens on home state governments and judicial systems. Critically, civil society actors will be given a role as both advocates and mediators in order to achieve a fair result for those impacted abroad by extractive enterprises. Compelling, engaging and timely, this book presents an innovative approach for regulating the foreign conduct of the extractive sector"--
Dark history -- The case for civil society and corporate actors -- Obstacles in holding corporations to account -- The United States -- Canada, the UK and Australia -- Utilising state-based and civil society sponsored mechanisms -- A new policy direction -- Accountability, effectiveness, and contrast.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Mining law; Mineral industries -- Law and legislation; Mines and mineral resources; Energy & natural resources law; Electronic books